What Proportion of Patients with Bone and Soft Tissue Tumors Contracted Coronavirus-19 and Died From Surgical Procedures During the Initial Period of the COVID-19 Pandemic? Results From the Multicenter British Orthopaedic Oncology Society Observational Study. Issue 5 (May 2021) - Rajasekaran, Raja Bhaskara; Ashford, Robert U.; Cosker, Thomas D. A.; Stevenson, Jonathan D.; Jeys, Lee; Pollock, Rob; Rankin, Kenneth S.; Cool, Paul; Patton, James T.; Whitwell, Duncan; Gibbons, Christopher L. M. H.; Carr, Andrew; et al.
Abstract: Background: Delivering uninterrupted cancer treatment to patients with musculoskeletal tumors has been essential during the rapidly evolving coronavirus 2019 (COVID-19) pandemic, as delays in management can be detrimental. Currently, the risk of contracting COVID-19 in hospitals when admitted for surgery and the susceptibility due to adjuvant therapies and associated mortality due to COVID-19 is unknown, but knowledge of these potential risks would help treating clinicians provide appropriate cancer care. Questions/purposes: (1) What is the risk of hospital-acquired COVID-19 in patients with musculoskeletal tumors admitted for surgery during the initial period of the pandemic? (2) What is the associated mortality in patients with musculoskeletal tumors who have contracted COVID-19? (3) Are patients with musculoskeletal tumors who have had neoadjuvant therapy (chemotherapy or radiation) preoperatively at an increased risk of contracting COVID-19? (4) Is a higher American Society of Anesthesiologists (ASA) grade in patients with musculoskeletal tumors associated with an increased risk of contracting COVID-19 when admitted to the hospital for surgery? Methods: This retrospective, observational study analyzed patients with musculoskeletal tumors who underwent surgery in one of eight specialist centers in the United Kingdom, which included the five designated cancer centers in England, one specialist soft tissue sarcoma center, and two centers from Scotland between March 12, 2020 and May 20, 2020. A total of 347 patients were included, with a median (range) age of 53 years (10 to 94); 60% (207 of 347) were men, and the median ASA grade was II (I to IV). These patients had a median hospital stay of 8 days (0 to 53). Eighteen percent (61 of 347) of patients had received neoadjuvant therapy (8% [27] chemotherapy, 8% [28] radiation, 2% [6 ] chemotherapy and radiation) preoperatively. The decision to undergo surgery was made in adherence with United Kingdom National Health Service and national orthopaedic oncology guidelines, but specific data with regard to the number of patients within each category are not known. Fifty-nine percent (204 of 347) were negative in PCR testing done 48 hours before the surgical procedure; the remaining 41% (143 of 347) were treated before preoperative PCR testing was made mandatory, but these patients were asymptomatic. All patients were followed for 30 days postoperatively, and none were lost to follow-up during that period. The primary outcome of the study was contracting COVID-19 in the hospital after admission. The secondary outcome was associated mortality after contracting COVID-19 within 30 days of the surgical procedure. In addition, we assessed whether there is any association between ASA grade or neoadjuvant treatment and the chances of contracting COVID-19 in the hospital. Electronic patient record system and simple descriptive statistics were used to analyze both outcomes. Results: Four percent (12 of 347) of patients contracted COVID-19 in the hospital, and 1% (4 of 347) of patients died because of COVID-19-related complications. Patients with musculoskeletal tumors who contracted COVID-19 had increased mortality compared with patients who were asymptomatic or tested negative (odds ratio 55.33 [95% CI 10.60 to 289.01]; p < 0.001).With the numbers we had, we could not show that adjuvant therapy had any association with contracting COVID-19 while in the hospital (OR 0.94 [95% CI 0.20 to 4.38]; p = 0.93). Increased ASA grade was associated with an increased likelihood of contracting COVID-19 (OR 58 [95% CI 5 to 626]; p < 0.001) Conclusion: Our results show that surgeons must be mindful and inform patients that those with musculoskeletal tumors are at risk of contracting COVID-19 while admitted to the hospital and some may succumb to it. Hospital administrators and governmental agencies should be aware that operations on patients with lower ASA grade appear to have lower risk and should consider restructuring service delivery to ensure that procedures are performed in designated COVID-19-restricted sites. These measures may reduce the likelihood of patients contracting the virus in the hospital, although we cannot confirm a benefit from this study. Future studies should seek to identify factors influencing these outcomes and also compare surgical complications in those patients with and without COVID-19. Level of Evidence: Level III, therapeutic study.